KEPUASAN MAHASISWA DALAM PELATIHAN PENINGKATAN KEPRIBADIAN DAN PERSONAL BRANDING DI FAKULTAS VOKASI UNIVERSITAS NEGERI SURABAYA - Nudin, Salamun; Fahmi, Hafizhuddin Zul; Winingsih, Evi; Rosy, Brillian; Fatoni, Fandi; Asmunin; Nurhidayat, Andy Iwan (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2025)
This article aims to analyze the level of student satisfaction with personality enhancement and personal branding training held at the Faculty of Vocational Studies, Surabaya State University. The method used is a survey by distributing questionnaires to students who have attended the training. The focus of the article covers aspects such as training content, teaching methods, interaction between students and instructor, and the positive impact felt by students after attending the training. The results of the analysis showed that most students were very satisfied with the personality enhancement and personal branding training they attended. Factors that contributed the highest to student satisfaction included the instructor mastery of the training material and the provision of disscussion opportunities, with 41 students very satisfied out of 55 students who attended the training. However, there are several aspects that need to be considered to increase student satisfaction, such as improving the comfort of the training room and adjusting the material to better suit the needs of students. The implication of these findings is the importance of higher education institutions to continuously improve and develop personality and personal branding training programs to meet students' expectations and needs. Improving the quality of training can contribute positively not only to students' personal development, but also to their overall learning experience.  Increasing student satisfaction in future training activities can be done by conducting a thorough evaluation to improve and adjust training materials to the needs of students. As well as creating a comfortable training environment to reduce communication barriers between students and instructor.